The Companions contribution to the Development of Poetry: إسهام الصحابة رضی الله عنهم في إنما الشعر - Saleem , Dr. Mufti Muhammad; Ahmad , Prof. Dr. Matloob; Ali , Dr. Wajid (Al Khadim Research Journal of Islamic Culture and Civilization, 2025)
This research artical “The Companions contribution to the Development of Poetry” is study to the companions contribution in the establishment of the Arabic poetry, Arabic is a semitic and ancient language, among the world languages, it is one of the languages of the united nations General assembly. For this reason, the united nations Educational, scientific and cultural organization decided to celebrate the international Day of the Arabic language on December 18 every year since 2012. It is one of the world languages of UNESCO. Spoken by more than 422 million people in the world, and used by more than a billion. And the half Muslims in the world. Although the Arabic langauge was used only in the limited circle of the Arab regions before the advent of Islam. However, after the rise of Islam, the arabic langauge was used only in the limited circle of the Arabic regions before the advent of Islam. However, after the rise of Islam, the Arabic languag spreal and became popular in various countries of the world, in addition to the Arabian peninsula, this was achieved with the contribution of the companions, may God be pleased with all them. The Islamic era also surpasses its importance with its supreme peak in the development of Arabic literature because they left poetry collection and letters, and Historians stories. It is a reference point for the language and a source of various arts.